1997
DOI: 10.1002/(sici)1098-1063(1997)7:1<88::aid-hipo9>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Orphanin FQ inhibits synaptic transmission and long‐term potentiation in rat hippocampus

Abstract: It is known that opioid peptides acting on opioid receptors can modulate hippocampal synaptic functions. Although a novel member of the opioid receptor family, ORL1 receptors, that displays high-sequence homology with classical opioid receptors is abundant in the hippocampus, little is known regarding its role in synaptic function. The present study was designed to investigate whether activation of the ORL1 receptor by its natural ligand, orphanin FQ, could modulate synaptic transmission and synaptic plasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 17 publications
2
25
2
1
Order By: Relevance
“…In contrast to the report of Yu et al (1997), OFQ/N application had no effect on ®eld EPSP slopes and moreover, we observed a similar effect of OFQ/N in rat hippocampal slices, i.e., inhibition of LTP induction without effect on ®eld EPSP slope. However, in agreement with Yu et al (1997), we observed a depression of evoked CA1 population spikes following application of OFQ/N (data not shown). Thus, it is likely that OFQ/N exerts a postsynaptic inhibitory action in CA1 pyramidal neurons, which could be mediated by activation of potassium conductances (Ikeda et al, 1997;Madamba et al, 1999) or inhibition of calcium currents (Kno¯ach et al, 1996).…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast to the report of Yu et al (1997), OFQ/N application had no effect on ®eld EPSP slopes and moreover, we observed a similar effect of OFQ/N in rat hippocampal slices, i.e., inhibition of LTP induction without effect on ®eld EPSP slope. However, in agreement with Yu et al (1997), we observed a depression of evoked CA1 population spikes following application of OFQ/N (data not shown). Thus, it is likely that OFQ/N exerts a postsynaptic inhibitory action in CA1 pyramidal neurons, which could be mediated by activation of potassium conductances (Ikeda et al, 1997;Madamba et al, 1999) or inhibition of calcium currents (Kno¯ach et al, 1996).…”
Section: Discussioncontrasting
confidence: 97%
“…Second, unlike OFQ/N, DAMGO is a stable analogue and peptidase inhibitors were not used in this study. Third, and perhaps most important, the receptor inactive analogue des-Phe 1 -OFQ/N (Matthes et al, 1996;Yu et al, 1997) did not decrease DA levels at the same 1 mM concentration. As des-Phe 1 -OFQ/N differs in structure from OFQ/N by one amino acid, the rate of recovery of this analogue is likely to be very similar and thus the dose of des-Phe 1 -OFQ/N is directly comparable.…”
Section: Discussionmentioning
confidence: 98%
“…Several OFQ fragments with high affinity binding to the ORL1 receptor also have been identified (Dooley et al, 1997). Binding of OFQ to the ORL1 receptor has been shown to stimulate ORL1-induced Ca 2ϩ and K ϩ conductance changes (Conner et al, 1996(Conner et al, , 1997Knoflach et al, 1996;Nicol et al, 1996;Vaughan and Christie, 1996;Abdulla and Smith, 1997; Vaughan et al, 1997;Yu et al, 1997;Wagner et al, 1998), protein kinase C activation (Lou et al, 1997), and to effect the function of other neurotransmitter systems (Faber et al, 1996;Giuliani and Maggi, 1996;Murphy et al, 1996;Wang et al, 1996;Gintzler et al 1997;Liebel et al, 1997;Inoue et al, 1998;Konya et al, 1998). Intraven-tricular injection of OFQ fails to produce cross-tolerance with morphine or conditioned place preference (Devine et al, 1996a), but it has been implicated in various modulatory effects of allodynia (Hara et al, 1997;Minami et al, 1997) and nociception (Grisel et al, 1996;Mogil et al, 1996a,b;Rossi et al, 1996 Xu et al, 1996;Dawson-Basoa and Gintzler, 1997;Heinricher et al, 1997;King et al, 1997;Liebel et al, 1997;Morgan et al 1997;Nishi et al, 1997;Tian et al, 1997a,b;Yamamoto et al, 1997;Zhu et al, 1997), enticing many to refer to this molecule as nociceptin.…”
Section: Indexing Terms: Receptor Autoradiography; In Situ Hybridizatmentioning
confidence: 99%
“…The role of orphanin in the hippocampus is presently not clear. However, orphanin has been reported to reversibly inhibit voltage-gated calcium channels in pyramidal neurons from area CA1 and CA3 (Knoflach et al, 1996) and to inhibit synaptic transmission and long-term potentiation in area CA1 of Ammon's horn and the dentate gyrus (Yu et al, 1997). The latter effect is thought to be presynaptic in nature.…”
Section: Orphanin Fq and Orl1 Receptor Circuitrymentioning
confidence: 99%